Penyutradaraan Film Mokumenter “Tradisi menjadi Prestasi” dengan Pendekatan Naratif dan Gaya Eksposisi - Antonius Kevin; Toto Sugito; Fajar Syuderajat (BADAN PENERBIT STIEPARI PRESS, 2025)
The mockumentary film Tradition Becomes Achievement was created as an informational and educational medium to reintroduce cultural values through traditional sports, particularly in West Java. This activity aims to address the declining interest of younger generations in traditional sports, which are increasingly displaced by digital culture. The method used in the film production applied a narrative approach and exposition style, involving the stages of pre-production, production, and post-production. The outcome of this activity demonstrates that the mockumentary film effectively delivers traditional sports content in an informative and visual format to the wider public via social media platforms such as YouTube. Therefore, the film serves as an alternative cultural communication strategy that supports the preservation of traditional sports in the digital era.